Entreprenurship and Small Scale Medium Enterprises in the South East, Nigeria - Sadiq, Sadiq Eche (African Multidisciplinary Journal of Sciences and Artificial Intelligence, 2025)
The study examined the effect of entrepreneurship and small scale medium enterprise sin the south east in Nigeria. entrepreneurship and small scale enterprises in the south east Nigeria. The study adopted the sectional survey design, thereby making the questionnaire the main instrument of data collection. The study employed the spearman’s rank order correlation method with the aid of SPSS 23.0 to analyse the formulated hypotheses. From the data analysis, the study revealed that marketing and distribution of product significantly affect sales performance of SMEs in south east Nigeria, there is significant relationship between entrepreneurship technology strategic and product innovation of SMEs in south east Nigeria; there is significant relationship between production strategic and competitive advantages of SMEs in south east Nigeria and there is significant relationship between learning strategic in entrepreneurship and product innovation of SMEs in south east Nigeria. It is therefore recommended that for SMEs to stay competitive, expand sales capabilities and innovative, SMEs should ally strategically through technology, learning, marketing and distribution enterprises.